2019
DOI: 10.3389/fimmu.2019.00143
|View full text |Cite
|
Sign up to set email alerts
|

Faecalibacterium prausnitzii Skews Human DC to Prime IL10-Producing T Cells Through TLR2/6/JNK Signaling and IL-10, IL-27, CD39, and IDO-1 Induction

Abstract: The human colonic mucosa contains regulatory type 1-like (Tr1-like, i.e., IL-10-secreting and Foxp3-negative) T cells specific for the gut Clostridium Faecalibacterium prausnitzii (F. prausnitzii), which are both decreased in Crohn's disease patients. These data, together with the demonstration, in mice, that colonic regulatory T cells (Treg) induced by Clostridium bacteria are key players in colon homeostasis, support a similar role for F. prausnitzii-specific Treg in the human colon. Here we assessed the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 43 publications
5
57
0
Order By: Relevance
“…B. longum strains have been demonstrated to cause changes in the level of specific Bifidobacterium species in the elderly that correlated with TNF-α, TGF-β, and IL-10 levels in serum [117]. The daily consumption of Bacillus coagulans BC30 PB spores has been shown to significantly increase the populations of Faecalibacterium prausnitzii, with concomitant increases in anti-inflammatory IL-10 levels in elderly subjects [118], supporting the direct correlation confirmed by another study [119]. B. coagulans BC30 has been confirmed in ex vivo experiments to increase the T-cell production of TNF-α in response to specific adenovirus and influenza virus exposures [71].…”
Section: Probioticssupporting
confidence: 66%
“…B. longum strains have been demonstrated to cause changes in the level of specific Bifidobacterium species in the elderly that correlated with TNF-α, TGF-β, and IL-10 levels in serum [117]. The daily consumption of Bacillus coagulans BC30 PB spores has been shown to significantly increase the populations of Faecalibacterium prausnitzii, with concomitant increases in anti-inflammatory IL-10 levels in elderly subjects [118], supporting the direct correlation confirmed by another study [119]. B. coagulans BC30 has been confirmed in ex vivo experiments to increase the T-cell production of TNF-α in response to specific adenovirus and influenza virus exposures [71].…”
Section: Probioticssupporting
confidence: 66%
“…The relationship between IDO and IL-10 may be particularly relevant in the presence of microbial invasion since some bacteria can induce DCs to facilitate IL-10 production by subpopulations of T cells such as the FoxP3-negative Tr1-like cells. This is achieved by the microbial induction of appropriate T cell polarizing molecules including IDO1 (189). Consistent with the overall anti-inflammatory balance which this generates, the production of IDO1 and IL-10 is accompanied by a reduction in the secretion of pro-inflammatory TNF-α and IL-12 components.…”
Section: Malaria and Trypanosomiasismentioning
confidence: 87%
“…27 In addition, it was demonstrated that tolerogenic effects induced by IDO-1 depend on TLR2/6-induced JNK signaling by Faecalibacterium prausnitzii and ectonucleotidase activity. 28 A key mechanism involved in mDCs-mediated immunosuppression is the expression of IDO-1. 31 The interaction of DCs with TLR2 and TLR4 treated with ES L1 (excretory-secretory muscle larvae) promotes the expansion of CD4 + CD25 high Foxp3 high producing IL-10 and TGF-cells in an IDO-1-dependent form.…”
Section: Discussionmentioning
confidence: 99%